1980
DOI: 10.1128/aac.18.6.868
|View full text |Cite
|
Sign up to set email alerts
|

Differences among Providencia species in their in vitro susceptibilities to five antibiotics

Abstract: Significant differences among the three Providencia species (P. alcalifaciens, P. stuartii, and P. rettgeri) in antimicrobial susceptibilities to five antibiotics were shown. P. stuartii was the most resistant of the three species, and P. alcalifaciens was the most susceptible. P. rettgeri was similar to P. stuartii in susceptibilities to cefoxitin, cephalothin, and cefamandole but differed in showing greater susceptibilities to tobramycin and gentamicin. Cefoxitin (16 jAg/ml) and cefamandole (16 yg/ml) inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

1982
1982
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
2
4
0
Order By: Relevance
“…Certain antimicrobials such as amikacin, ampicillin/sulbactam, aztreonam, cefazolin, cefepime, cefotetan, cefoxitin, ceftazidime, and cephalothin showed two-fold reduction in MIC values in all the treated groups as compared to the control. The control MIC values of cefoxitin (>16 µg/mL) and cephalothin (>16 µg/mL) were well matched with literature reported data [17]. In this experiment, the MIC values of cefoxitin and cephalothin were reduced by two-fold after biofield energy treatment in both lyophilized as well as revived treated groups as compared to the control.…”
Section: Antimicrobial Susceptibility Testsupporting
confidence: 89%
“…Certain antimicrobials such as amikacin, ampicillin/sulbactam, aztreonam, cefazolin, cefepime, cefotetan, cefoxitin, ceftazidime, and cephalothin showed two-fold reduction in MIC values in all the treated groups as compared to the control. The control MIC values of cefoxitin (>16 µg/mL) and cephalothin (>16 µg/mL) were well matched with literature reported data [17]. In this experiment, the MIC values of cefoxitin and cephalothin were reduced by two-fold after biofield energy treatment in both lyophilized as well as revived treated groups as compared to the control.…”
Section: Antimicrobial Susceptibility Testsupporting
confidence: 89%
“…In accordance with previous observations [25,26], most of the P. alcalifaciens isolates studied were sensitive to several antimicrobial drugs. Although multiple resistance to ampicillin, co-trimoxazole, sulphamethoxazole and tetracycline was observed in some isolates, no correlation between antibiotic resistance and the presence of a particular plasmid could be demonstrated.…”
Section: Discussionsupporting
confidence: 73%
“… 4 More than 60% of P. stuartii isolates were found to be sensitive to aminoglycosides (gentamicin, streptomycin, and tobramycin), penicillin (amoxicillin, Augmentin, and ampicillin). 5–7 This substantial evidence revealed that P. stuartii is not intrinsically resistant to the aforementioned antibiotics (Ampicillin, Gentamicin, and Tobramycin) at this time. (b) Further, this study reported 16.7% (1 out of 6 strains) resistance in Streptococcus pneumoniae to penicillin.…”
Section: Dear Editormentioning
confidence: 84%
“…2 Moreover, intrinsic resistance is highly important as it along with another resistance mechanism may result in poor clinical outcomes. 4 , 5 …”
Section: Dear Editormentioning
confidence: 99%